Parent material modulates land use effects on soil organic carbon fractions but not inorganic carbon in subtropical red soils - Rui Jiang; Shuai Liu; Yu Zhang; Enze Xie; Beibei Fan; Fahui Jiang; Samuel Adingo; Lei Gao; Xinhua Peng (Soil and Tillage Research, 2026)

Instability-driven flame propagation dynamics of premixed hydrogen-ammonia deflagration in a closed duct with obstacles - Rui Xie; Zhi Wang; Xianyu Yu; Liuqian Zhu; Yang Lin; Junyi Li; Bobo Shi (Fuel, 2026)

Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Euglena gracilis and paramylon attenuate hyperuricemia and protect against renal injury in mice - Tao Yu; Kaikai Zhang; Rui Hang; Weiliang Wang; Jingli Xie; Wenmin Bai; Yuanguang Li; Minxi Wan (Food Bioscience, 2026)

A Variogram Model Based on Spatial Decay of Gravity Anomaly Covariance - Xiao-yu Xie; Kai-xin Luo; Ju-liang Cao; Shao-kun Cai; Rui-hang Yu; Qi-qin Hu; Yan Guo; Bai-nan Yang (Applied Geophysics, 2026)

Structure, assembly, and biological assessment of microbial communities based on eDNA metabarcoding in the continuous river-estuary-sea system of the Yellow River Estuary, China - Gang Xie; Xiaoxia Yu; Ning Zhang; Jie Li; Rui Wang; Yu Wang; Xinlei Li; Dan Li; Wanting Wang; Shilong Ren; Yi Zhu; Guoqiang Wang (Marine Pollution Bulletin, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Defect-engineered nitrogen-doped carbon from tannic acid for highly efficient peroxydisulfate activation via nonradical pathways - Rui Luo; Tong Yu; Kexin Tai; Xiaoju Wen; Zongtang Liu; Binbin Qian; Qihui Xu; Haijiao Xie; Xiankun Wu (Journal of Environmental Chemical Engineering, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Associations between domestic water hardness and incident type 2 diabetes and the mediating role of metabolomics - Hanwen Zhou; Sicheng Li; Keyang Li; Wenlong Li; Yingcheng Liu; Rui Yu; Xufeng Xian; Wei Zheng; Xiaoni Zhong; Biao xie (Environmental Pollution, 2026)

Spinal Cord CELF4 in Chronic Constriction Injury-Induced Neuropathic Pain: Association with TRPV1 and COX-2 Expression - Guanxiang Kong; Rui Tan; Xianming Zeng; Hailong Zhang; Bin Zhang; Jiasheng Yu; Rushan Xie (Journal of Molecular Neuroscience, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Mechanistic insights into low-temperature NH3-SCR over Mn-based Zr-pillared montmorillonite (Mn/Zr-PILM): Synergistic catalysis revealed by experiments and DFT - Ziwen Zheng; Huaqing Xie; Zhenyu Yu; Bin Xiao; Qingbo Yu; Kun Wang; Jiabo Zhao; Haijian Xu; Rui Guo (Process Safety and Environmental Protection, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

Efficient fabrication of micro/nanostructured porous film integrating excellent radiative cooling, robust water repellence and unidirectional moisture permeability by micro extrusion roll forming - Yunjia Cai; Yu Du; Yingying Chen; Rui Tong; Feicong Fan; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Peroxisome proliferator-activated receptor gamma prevents activation of RBL-2H3 cells by inhibiting FcεRI-mediated signal transduction - Yu Zhang; Suyu Ruan; Yuhang Xie; Xiaoqing Rui; Jianjun Zhou; Weihua Wang (Inflammation Research, 2025)

Mo-Nitrogen nexus: Nanotechnology enhanced Mo-based nitrogen fixation towards environmental sustainability - Samina Irshad; Yu Xie; Yaping Lyu; Ziqi Zhang; Xingxin Liu; Haojie Wei; Beza Tuga; Christy L. Haynes; Yaqi Jiang; Yi Sun; Jason C. White; Yukui Rui; et al. (Chemical Engineering Journal, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Molecular detection and phylogenetic analysis of lumpy skin disease virus in Yunnan Province, China from 2019 to 2023 - Jun Yao; Xue Li; Lei Tan; Lin Gao; Pei Zhu; Jiarui Xie; Rui Yan; Taoyin Yu; Fengyi Xia; Qiyun Chen; Bangquan Zeng; Jiaping Yang (Veterinary Research Communications, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

MLWNNR: LncRNA-Disease Association Prediction with Multi-Kernel Learning-Driven Weighted Nuclear Norm Regularization - Guo-Bo Xie; Hao-Jie Xu; Guo-Sheng Gu; Zhi-Yi Lin; Jun-Rui Yu; Rui-Bin Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Life-long impacts of nanoplastics to rice plant (Oryza sativa L.): Decreased grain yield with perturbed metallome and soil microbiome - Hongxin Xie; Xuejia Wang; Liwei Cui; Rui Chen; Rui Zhao; Yang Yu; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2025)

Deciphering cadmium effects on biodegradation of triphenyl phosphate in sediments: Insights from molecular biology and computational chemistry - Dandan Li; Xiaoyu Wang; Chen Xie; Ziwu Fan; Rui Ding; Songqi Liu; Yu Chen; Kai Yu (Journal of Hazardous Materials, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

An innovative and efficient approach for slope reliability analysis: Machine learning based surrogate modeling with advanced attention mechanisms - Nenghao Huang; Yu Han; Weiwei Xie; Rui Hu; Hao Peng; Guanxian Song; Menglan Wu; Menglong Zhu; Hua Wei; Ming Liang (Engineering Geology, 2025)

Responses of an invasive plant Alternanthera philoxeroides to cadmium, nutrient availability and water temperature - Zi-Yang Xie; Zhi-Hang Liu; Xin-Yue Gu; Yuan-Yuan Qin; Yu-Ting Du; Jin Yan; Rui Zhang; Chao Si (Aquatic Botany, 2025)

SfM on-the-fly: A robust near real-time SfM for spatiotemporally disordered high-resolution imagery from multiple agents - Zongqian Zhan; Yifei Yu; Rui Xia; Wentian Gan; Hong Xie; Giulio Perda; Luca Morelli; Fabio Remondino; Xin Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Contributions of diffusion and ebullition processes to total methane fluxes from a subtropical rice paddy field in southeastern China - Tingting Zhu; Yanlian Zhou; Weimin Ju; Yu Mao; Rui Xie (Agricultural and Forest Meteorology, 2025)

Two new phenolic glycosides from the rhizomes of Paris yunnanensis - Yu-Rui Xie; Shan-Shan Ling; Yan-Xi Li; Mei-Ru Wang; Hai-Yang Liu (Phytochemistry Letters, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Carvacrol acts on the larval midgut of Spodoptera frugiperda by destroying the tissue structure and altering the bacterial community - Jingjing Zhang; Cuiting Liu; Xinyi Xie; Xuanyue Yu; Yuting Huang; Rui Tang; Jian Zeng; Benshui Shu (Journal of Asia-Pacific Entomology, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

General synthesis of porous metal oxides nanosheets for gas sensing by gradient crystallization induced spatial confinement approach - Xuan-Yu Yang; Rui-Jie Zhao; Fei-Long Gong; Ke-Feng Xie; Hua Xu; Yong-Hui Zhang (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Minimization of entropy generation rate in hydrogen iodide decomposition membrane reactor - Rui Kong; Lingen Chen; Shaojun Xia; Zhihui Xie; Yu Lin (Journal of Cleaner Production, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Microplastic-mediated environmental behavior of metal contaminants: mechanism and implication - Yu Xie; Samina Irshad; Yaqi Jiang; Yi Sun; Yukui Rui; Peng Zhang (Environmental Science and Pollution Research, 2024)

3D gravity inversion using cycle-consistent generative adversarial network - Shu-Bo Qiao; Hou-Pu Li; Rui Qi; Yu-Jie Zhang; Shi-Min Xie (Applied Geophysics, 2024)

Influence of the anchor angle on the seismic response of anchored stabilizing piles: Centrifuge modeling tests - Yu Wang; Tong Zheng; Rui Sun; Zhiliang Sun; Zhinan Xie; Zhendong Shan; Hongshuai Liu; Wenhao Qi; Yu Bai (Soil Dynamics and Earthquake Engineering, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

Preparation of conjugated linoleic acid-rich oleogel emulsions by dynamic high-pressure microfluidization technology - Dianyu Yu; Na Li; Rui Wang; Wenlin Xue; Donghua Wang; Walid Elfalleh; Lanxia Qin; Fengying Xie (Journal of Food Engineering, 2024)

Improving on mapping long-term surface water with a novel framework based on the Landsat imagery series - Ling Lan; Yu-Ge Wang; Hao-Shuang Chen; Xu-Rui Gao; Xie-Kang Wang; Xu-Feng Yan (Journal of Environmental Management, 2024)

Highly-efficient hydrogen production from ammonia decomposition over Co-doped graphdiyne under moderate temperature - Lishan Liu; Feng Gong; Yunlong Xie; Sijun Wang; Yu Qiu; Zhihua Wang; Rui Xiao (Fuel, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Distribution, sources, and potential health risks of fluoride, total iodine, and nitrate in rural drinking water sources of North and East China - Shier Huang; Jiaxun Guo; Yu Xie; Rui Bian; Nan Wang; Weixiao Qi; Huijuan Liu (Science of The Total Environment, 2023)

Whole-genome analysis of the benzoic acid-degrading bacterium Bacillus halotolerans B28 to reveal its phytoprobiotic effects - Dandan Wang; Li Sun; Hong Yu; Chengkai Zhang; Xin Guan; Mengliang Wang; Rui Cheng; Chao Wang; Zhihong Xie (International Biodeterioration & Biodegradation, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Molten Salt-Mediated Surface Reconstruction Induced Orientation-Growth of 1D/2D Heterostructure for High-Sensitivity H2S Gas Sensing - Xuan-Yu Yang; Rui-Jie Zhao; Ke-Feng Xie; Hua Xu; Shao-Ming Fang; Yong-Hui Zhang (Chemical Engineering Journal, 2023)

Analytical study on heavy metal output fluxes and source apportionment of a non-ferrous smelter in southwest China - Chenchen Li; Peng Dong; Jin Yan; Rui Gong; Qi Meng; Jun Yao; Hanjing Yu; Yaoqiang Ma; Bang Liu; Ruosong Xie (Environmental Pollution, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Microorganisms, their residues, and soil carbon storage under a continuous maize cropping system with eight years of variable residue retention - Xuefeng Zhu; Hongtu Xie; Michael D. Masters; Yichao Rui; Yu Luo; Hongbo He; Xudong Zhang; Chao Liang (Applied Soil Ecology, 2023)

Improvement and application of UNet network for avoiding the effect of urban dense high-rise buildings and other feature shadows on water body extraction - Yiheng Xie; Renxi Chen; Mingge Yu; Xiaoping Rui; Xiaomin Du (International Journal of Remote Sensing, 2023)

China's optimal development pathway of intermittent renewable power towards carbon neutrality - Bai-Chen Xie; Rui-Yu Zhang; Xian-Peng Chen (Journal of Cleaner Production, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water - Chun Cai; Yangfan Liu; Rui Xu; Jiaheng Zhou; Jin Zhang; Yu Chen; Lingyu Liu; Lexiang Zhang; Shuping Kang; Xianjun Xie (Chemosphere, 2023)

Microplastics perturb colonic epithelial homeostasis associated with intestinal overproliferation, exacerbating the severity of colitis - Shuang Xie; Rui Zhang; Zhaoyan Li; Chunru Liu; Yanyu Chen; Qinghua Yu (Environmental Research, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Regulation of Social Memory by Lateral Entorhinal Cortical Projection to Dorsal Hippocampal CA2 - Rui Dang; Yu Zhou; Yue Zhang; Die Liu; Miao Wu; An Liu; Zhengping Jia; Wei Xie (Neuroscience Bulletin, 2022)

Inactivation and Removal Technologies for Algal-Bloom Control: Advances and Challenges - Ming-ming Zhan; Pei-rui Liu; Xiao-ya Liu; Yu Hong; Xing Xie (Current Pollution Reports, 2021)

Characteristics, Sources, and Risks of Polycyclic Aromatic Hydrocarbons in Topsoil and Surface Water from the Liuxi River Basin, South China - Zhenglan Xie; Lei Gao; Zuobing Liang; Jianyao Chen; Shaoheng Li; Aiping Zhu; Yu Wu; Zhigang Yang; Rui Li; Zhuowei Wang (Archives of Environmental Contamination and Toxicology, 2020)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

Genotoxicity and cytotoxicity reduction of the polluted urban river after ecological restoration: a field-scale study of Jialu River in northern China - Jie Sun; Rui Zhang; Long Qin; Haixiao Zhu; Yu Huang; Yingang Xue; Shuqing An; Xianchuan Xie; Aimin Li (Environmental Science and Pollution Research, 2017)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Characterization of LHY-821, a novel moderately differentiated endometrial carcinoma cell line - Qian Hu; Li Yu; Rui Chen; Yan Zhang; Ya Xie; Qinping Liao (In Vitro Cellular & Developmental Biology - Animal, 2012)

Evaluation of the Use of SCAR Markers for Screening Genetic Diversity of Lentinula edodes Strains - Jing-Yu Liu; Zheng-He Ying; Fang Liu; Xin-Rui Liu; Bao-Gui Xie (Current Microbiology, 2012)

Bacterial communities in PAH contaminated soils at an electronic-waste processing center in China - Wen Zhang; Hui Wang; Rui Zhang; Xie-Zhi Yu; Pei-Yuan Qian; M. H. Wong (Ecotoxicology, 2010)